Effect of electrolyte on synergism of anionic-surfactant mixture - Othman, N.; Ahmad, A.; Piramali, M. A. (2009)

(untitled)
Demulsification is one of the key processes in emulsion liquid membrane application. This study involved the effect of electrical field on demulsification of water in oil using batch high voltage demulsifier system. This technique widely used because of its advantages of easy manipulation of applied field direction and strength, offers cost–effective separation and minimal environmental impact combined with mechanical simplicity. Influence of various values of frequency (400–1500 Hz) and voltage was studied experimentally using Alternate Current (AC) High Voltage Demulsifier with insulated electrode. The emulsion consists of kerosene as organic phase, sulfuric acid as internal phase and span 80 (3 and 5 w/v %) as a surfactant. The effect of emulsion preparation such as homogenizer speed, internal phase and surfactant concentrations on the stability of water–in–oil emulsion was also investigated. The results showed that the attractive forces between the water droplets under an electrical field increase by raising the applied electrical field strength. Meanwhile, the time required for the emulsion to separate and coalescence under electrical field increased when the stability of emulsion increased